2020
DOI: 10.1042/bcj20200488
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-beta oligomers induce Parkin-mediated mitophagy by reducing Miro1

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disease associated with the accumulation of amyloid-beta oligomers (AβOs). Recent studies have demonstrated that mitochondria-specific autophagy (mitophagy) contributes to mitochondrial quality control by selectively eliminating the dysfunctional mitochondria. Mitochondria motility, which is regulated by Miro1, is also associated with neuronal cell functions. However, the role played by Miro1 in the mitophagy mechanism, especially relative to AβOs and neurodegene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 57 publications
2
15
0
Order By: Relevance
“…Therefore, we examined the mitochondrial function of cells in the AD model. Consistent with another previous study ( Kam et al, 2020 ), we also found that MMP was greatly reduced in the AD model based on JC-1 staining when compared to the control group. In addition, intracellular ROS was mainly generated in mitochondria, and dysfunctional mitochondria can cause disproportionate ROS generation.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, we examined the mitochondrial function of cells in the AD model. Consistent with another previous study ( Kam et al, 2020 ), we also found that MMP was greatly reduced in the AD model based on JC-1 staining when compared to the control group. In addition, intracellular ROS was mainly generated in mitochondria, and dysfunctional mitochondria can cause disproportionate ROS generation.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, intracellular ROS was mainly generated in mitochondria, and dysfunctional mitochondria can cause disproportionate ROS generation. Further, previous studies have shown that ROS levels in neuronal cells are upregulated in AD ( Butterfield and Halliwell, 2019 ; Kam et al, 2020 ). Our results demonstrated that Aβ treatment can stimulate both intracellular and mitochondrial ROS production.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…To investigate possible changes in Cytc, Drp1, Hsc70, and Lamp2a in the context of glutamate-induced neuronal excitotoxicity, we performed immunocytochemistry according to a previous study [ 54 ]. Cells (1 × 10 5 ) were seeded into 24-well microplates and fixed with 4% paraformaldehyde in PBS.…”
Section: Methodsmentioning
confidence: 99%